BUDAYA PENYIARAN TELEVISI DI INDONESIA - Mustika, Rieka (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2012)
This article is about cultural construction as a result of television broadcasting in Indonesia. Approach in the discussion of this article conducted a literature study issues relating to the topic of this article. In the case of commercial television, the dynamics of the economy proved more decisive in constructing a culture. Dynamic economic mechanism has made the showing of television culture, both organizationally and institutionally.